Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

Single-cell omics in plants: technological advances and biological insights - Yi Chen; Yige Dong; Jindi Yang; Zhe Liu; Shengyu Rong; Qiulei Lang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Applying semi-supervised learning algorithms in real-environment solid waste classification - Dong–Ying Lan; Pin–Jing He; Hui–Huang Zou; Rong–Rong Kan; Yi Wang; Fan Lü; Hua Zhang (Resources, Conservation and Recycling, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

AIEgen-based porous organic polymer-Ag nanoparticles hybrids with coreaction accelerator amplification and covalent rigidification-enhanced electrochemiluminescence for aflatoxin M1 detection - Jun-Qi Song; Qiu-Yi Peng; Mei-Ling Lu; Shu-Zhen Gao; Wen-Bin Liang; Shaoguang Sun; Ruo Yuan; Dong-Rong Xiao (Food Chemistry, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

O304 is a mitochondrial uncoupler which extends C. elegans lifespan and induces vasorelaxation of rat mesenteric arteries - Wen-Feng Li; Yi Zeng; Yi-Dan Zhang; Rong Zhang; Jing Lang; Wen-Jie Bu; Meng-Ke Zhao; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Bio-organic fertilizer amendment helps suppress tomato bacterial wilt disease by improving aggregation and enhancing the pathogen inhibition capacity within micro-aggregates - Menghui Dong; Eiko E. Kuramae; Mengli Zhao; Yi Min; Shanshan Liu; Xu Xu; Qirong Shen; Rong Li; George A. Kowalchuk (Biology and Fertility of Soils, 2025)

Room temperature natural light promoted DMSO/O2-catalyzed N-acylation reaction of imidazoles/triazoles with cyclopropenones - Guo-Dong Shen; Zhi-Rong Zhao; Kun Bi; Yi Man; Jun-Tong Liu; Xian-Qiang Huang; Xin Lv (Molecular Diversity, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Inhalable dexamethasone-loaded zwitterionic nanomicelles enabling effective penetration of the mucus barrier for acute lung injury treatment - Rong Chen; Xiangrong Dai; Rongjiao Sun; Yi Liao; Jiajia Dong; Ying Tan; Xuru Jin (Chemical Engineering Journal, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Inhibition of fungal mycelial growth and mycotoxin production using ZnO@mSiO2 nanocomposite during maize storage - Song-Yue Xu; Zi-Yi Wang; Qiong Wu; Feng-Wei Hu; Jin-Feng Zhao; Yu-Rong Zhang; Dong-Dong Zhang (Food Bioscience, 2025)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Tertiary treatment of municipal wastewater in an IBFR dominated by PD/A with unique niche - Yue-ning Wang; Shi-rong Dong; Hui-long OuYang; Ting Yang; Yi Wang (Chemosphere, 2024)

Excessive fluoride induces ovarian function impairment by regulating levels of ferroptosis in fluorosis women and ovarian granulosa cells - Nan Geng; Siyuan Dong; Pengpeng Xie; Yi Zhang; Rong Shi; Chen Chen; Zhao Xu; Qun Chen (Reproductive Toxicology, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Influence of GI configurations and wall thermal effects on flow structure and pollutant dispersion within urban street canyons - Peng-Yi Cui; Rong Ji; Lai He; Zhen Zhang; Yang Luo; Yong Yang; Yuan-Dong Huang (Building and Environment, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Four new phenolic glycosides from Dobinea delavayi - Xiu-Rong Wu; Li-Juan Lang; Yi Shen; Xiang Dong; Chao-Jiang Xiao; Bei Jiang (Natural Product Research, 2023)

Role of quorum sensing-based regulation in development of anaerobic ammonium oxidation process - Jun-Hui Yang; Dong-Qi Huang; Yin-Ce Geng; Yi-Rong Ling; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2023)

Microstructural Differences of the Cerebellum-Thalamus-Basal Ganglia-Limbic Cortex in Patients with Somatic Symptom Disorders: a Diffusion Kurtosis Imaging Study - Liao Dong; Huai-Bin Liang; Jiaxin Du; Yingying Wang; Qichen Zhou; Ziyue Xin; Yue Hu; Yi-Sheng Liu; Rong Zhao; Yuan Qiao; Chenglin Zhou; Jian-Ren Liu; et al. (The Cerebellum, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Mixing overstory tree- and understory fern-derived dissolved organic carbon produces non-additive effects on biodegradation in subtropical forests of southern China - Su-Li Li; Zhi Zheng; Yi-Dong Ding; Jia-Wen Xu; Rong Mao (Plant and Soil, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Tree mycorrhizal effect on litter-leached DOC amounts and biodegradation is highly dependent on leaf habits in subtropical forests of southern China - Yi-Dong Ding; Xin-Yi Xie; Jing-Hao Ji; Qian-Qian Li; Jia-Wen Xu; Rong Mao (Journal of Soils and Sediments, 2021)

Reconstruction method of irregular seismic data with adaptive thresholds based on different sparse transform bases - Hu Zhao; Tun Yang; Yu-Dong Ni; Xing-Gang Liu; Yin-Po Xu; Yi-Lei Zhang; Guang-Rong Zhang (Applied Geophysics, 2021)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Bidirectional Regulatory Mechanisms of Jaceosidin on Mitochondria Function: Protective Effects of the Permeability Transition and Damage of Membrane Functions - Wen-Rong Fu; Ji-Lei Chen; Xue-Yi Li; Jia-Xin Dong; Yi Liu (The Journal of Membrane Biology, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

The Effect of Bisphenol A on Growth, Morphology, Lipid Peroxidation, Antioxidant Enzyme Activity, and PS II in Cylindrospermopsis raciborskii and Scenedesmus quadricauda - Rong Xiang; Junqiong Shi; Yi Yu; Hongbo Zhang; Congcong Dong; Yanjun Yang; Zhongxing Wu (Archives of Environmental Contamination and Toxicology, 2018)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Detection of brown planthopper infestation based on SPAD and spectral data from rice under different rates of nitrogen fertilizer - Jian-Rong Huang; Jia-Yi Sun; Huai-Jian Liao; Xiang-Dong Liu (Precision Agriculture, 2015)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Effect of fungal fusaric acid on the root and leaf physiology of watermelon (Citrullus lanatus) seedlings - Hong-sheng Wu; Xiao-ming Yin; Dong-yang Liu; Ning Ling; Wei Bao; Rong-rong Ying; Yi-yong Zhu; Shi-wei Guo; Qi-rong Shen (Plant and Soil, 2008)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Status, causes and combating suggestions of sandy desertification in qinghai-tibet plateau - Yi-hua Liu; Guang-rong Dong; Sen Li; Yu-xiang Dong (Chinese Geographical Science, 2005)